Critical studies on bond strengths of masonry units - P. Nandurkar, B; A. M. Pande, Dr (International Journal of Engineering and Technology, 2018)
Performance of masonry is normally attributed to compressive strength of individual units, water absorption of individual units, strength of masonry mortar and the bond between mortar and individual units. Many researches in the past have contributed towards the bond strength and relevance of compressive strength of mortar in achieving good bonds. However, the quality of bricks available in India significantly vary from region the region. Thus, a need is felt in understanding bond strength of masonry. In this paper three types of mortars(total nine combinations), two types of bricks (red clay brick and fly ash brick) are considered, tests such as compressive strength, water absorption of the bricks, compressive strength of various mortar combinations, flexure bond strength and shear bond strength are presented. Failure patterns of the masonry units are also discussed. Results of the two tests show noticeable variation in bond strengths, however the shear bond strength has significant relationship with the compressive strength of mortar. The research outcome also points towards using bricks in saturated condition for achieving adequate performance.Â Â